HOSPITALISASI MEMPENGARUHI TINGKAT KECEMASAN ANAK TODDLER - Zulhaini Sartika A. Pulungan; Edi Purnomo; Arni Purwanti A. (Jurnal Kesehatan Manarang, 2017)
Hospitalization can cause anxiety and stress at all age levels. The cause of anxiety is influenced by many factors, both from the officer factor (nurses, doctors and other health personnel), the new environment, and the accompanying family during the treatment. Children sometimes perceive hospitalization as punishment so that children will feel shame, guilt, or fear. This leads to aggressive reactions such as anger and rebellion, verbal expression by saying angry words, not cooperating with nurses, thus affecting the treatment process while in hospital. The present study aimed at investigating the effect of hospitalization on anxiety levels of toddler in Puskesmas Tampa Padang. This research is an descriptive research with cross sectional design. Research subjects taken by purposive sampling counted 63 people. The data were analyzed using fisher's exact test. The results showed that hospitalization influenced toddler child's anxiety level (p 0.005). It is expected that health workers continue to provide good services and continue to maintain communication to children and families so that children feel comfortable during the process of hospitalization.